CLINICAL AND FUNCTIONAL OUTCOMES IN PATIENTS WITH DISTAL TIBIAL FRACTURE TREATED BY CIRCULAR EXTERNAL FIXATION - HASSAN, SMT; SAUD, AM; KHAN, AGS; ALI, R; ZEB, SA; RAZA, T; AHMED, A (Biological and Clinical Sciences Research Journal, 2024)
The method of circular external fixation arises as a wide type of treatment for these fractures, bringing advantages of stability of the fracture, keeping soft tissue integrity and early rehabilitation. Objectives: The main objective of the study is to find the clinical and functional outcomes in patients with distal tibial fractures treated by circular external fixation. methods: This retrospective study was conducted at Abwa Medical College Faisalabad from January 2023 to October 2023. Data were collected from 80 patients with distal tibial fractures. Data were collected according to the inclusion and exclusion criteria of the study. Clinical and demographic data were extracted from electronic medical records and radiographic imaging studies. Data also contain patient age, gender, mechanism of injury, fracture classification, AO/OTA classification, soft tissue injury severity, comorbidities, smoking status, and preoperative functional status. Results: Data were collected from 80 patients. The mean age of the patients was 45 ± 12.5 years. Out of 80, 55 (68.8%) were male and 25 (31.3%) female patients. The main mechanism of injury was road traffic accidents containing 40 (50%), falls from height 25 (31.3%) and sports related injuries 15 (18.8%). Rabe of motion shows a significant increase as compared to preoperative as 30 ± 10 degrees to 45 ± 15 degrees. Pain score was also decreasing from 7.5 ± 2.0 to 2.0 ± 1.5.Conclusion: It is concluded that circular external fixation demonstrates favourable clinical and functional outcomes in patients with distal tibial fractures, with high fracture union rates and significant improvements in range of motion and pain scores.